Perancangan Sistem Tracking Produksi Berbasis Website Menggunakan Framework Codeigniter Pada CV. Baretta Cemerlang - Arief Kurniawan; Muhammad Nawawi; Ramadhan Eka Syahputra; Saprudin (CV. Shofanah Media Berkah, 2023)
The rapid development of technology has had an impact on various areas of human life, including the world of business and the world of work. In today's era, companies are trying to increase work productivity and efficiency by utilizing technology. CV. Baretta Cemerlang, a manufacturer of ceramic tableware, faces challenges in optimizing its production process. In the current situation, every marketing must continuously contact the admin to get information on production progress. This is inefficient and makes work unproductive. Therefore the aim of this research is to develop a system with the right design and we call it a website-based production tracking system using the CodeIgniter framework. This production tracking system makes it easy for all company stakeholders to view, monitor, and update production status quickly and accurately. This system is also equipped with a real-time monitoring feature that enables fast and accurate decision making. With this system, companies can increase productivity, reduce production time, improve efficiency, and reduce human errors in production scheduling and control. This production tracking system has been integrated with the DBMS and can be accessed via a laptop/PC or mobile device. In this study it was concluded that the production tracking system is an effective solution to increase the efficiency and productivity of the company. However, the implementation of this system needs to be done carefully and pay attention to all elements related to it. It is hoped that the designed production tracking system will have a major positive impact on the company by increasing the efficiency of production performance. and ensure efficiency in various matters.